What Were Bulletin Board Systems? Looking Back At Pre-Internet Online Communication in Turkey - Furman, Ivo Ozan (My University, 2024)
As an online communication technology predating the Internet, Bulletin Board Systems (BBSs) are considered to be precursors of modern-day social media. Despite being a popular technology of its era both in Türkiye and abroad, BBS technologies tend to be entirely overlooked in historical accounts of online communication. This article begins with an overview on the history of BBS technologies both in Türkiye and abroad. It then introduces the HitNet archive, currently the only publicly accessible Turkish language BBS archive in the world. Using applied content analysis, the article then explores whether contents of the HitNet archive align with the findings of international academic literature on global BBS usage. The findings of paint a mixed picture wherein certain aspects of the HiTNet archive present a mixed picture that both affirms as well as contradicts academic literature. On one hand there are elements affirming the hyperlocal nature of BBS networks (message contents, unique topics for each server). On the other, there are mutual elements (humour) that complicate the framing of Turkish BBSs as hyperlocal entities. Accordingly one can tentatively argue that HiTNet users, while bound to their local geographical context, belonged to a relatively homogenous demographic (male university students and computing enthusiasts). Unfortunately, the findings of this article are not generalizable for all HiTNet users due to very limited nature of the sample studied. Furthermore, the lack of accessible archives means that it is increasingly difficult to access BBS content from the period dating from 1990-1997. The article concludes by stressing that archival research needs to be urgently undertaken in Türkiye to catalog what remains from the BBS era. If no action is taken, there is a risk of losing access to all online communication between 1990 and 1997.